Analysis of Numeracy Ability of Class VI Students at State 2 Elementary School of Kotamobagu - Katuuk, Deitje Adolfin; Kowal, Marsela Vera; Majaan, Telly (International Journal of Information Technology and Education, 2024)
This research aims to analyze students’ numeracy abilities in elementary schools. The research used is quantitative research with experimental methods. The subjects in this research were class VI students at SDN 2 Kotamobagu involving PPG Daljab UNIMA Category 1 Batch 2 students as actors in the learning process and researchers acting as observers in the research. Data collection techniques use learning outcomes evaluation tests and observations regarding students’ skills and attitudes during the learning process. The instruments used are evaluation test questions consisting of 5 questions and a skills observation sheet consisting of 3 assessment aspects, namely measurement, modeling, and presentation. As well as observing students’ attitudes which consist of 3 aspects, namely activeness, cooperation, and creativity. Data analysis in this research uses the Rasch Model. The research results show that numeracy ability is an ability that needs to be continuously improved and is not enough if only applied once or twice. Numeracy skills require continuous habituation and appropriate instruments or measuring tools to stimulate increased numeracy skills.